2019
DOI: 10.1142/s0219530519500015
|View full text |Cite
|
Sign up to set email alerts
|

Inverse scattering for a random potential

Abstract: In this paper we consider an inverse problem for the n-dimensional random Schrödinger equation (∆ − q + k 2 )u = 0. We study the scattering of plane waves in the presence of a potential q which is assumed to be a Gaussian random function such that its covariance is described by a pseudodifferential operator. Our main result is as follows: given the backscattered far field, obtained from a single realization of the random potential q, we uniquely determine the principal symbol of the covariance operator of q. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 61 publications
1
71
0
Order By: Relevance
“…, the random function is a distribution in f ∈ W s− d 2 −ǫ,p for any ǫ > 0 and p ∈ (1, ∞) (cf. Lemma 2.6), which is rougher than those considered in [9,15,20,21]; (2) if σ = 0 and s ∈ [ d 2 , d 2 + 1), the results obtained in this paper coincides with the ones given in [20]. The paper is organized as follows.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…, the random function is a distribution in f ∈ W s− d 2 −ǫ,p for any ǫ > 0 and p ∈ (1, ∞) (cf. Lemma 2.6), which is rougher than those considered in [9,15,20,21]; (2) if σ = 0 and s ∈ [ d 2 , d 2 + 1), the results obtained in this paper coincides with the ones given in [20]. The paper is organized as follows.…”
supporting
confidence: 71%
“…The white noise model can also be found in [6] and [5] for the one-dimensional problem and the stochastic elastic wave equation, respectively. Recently, the model of a generalized Gaussian field was developed to handle random processes [9,15]. The random function is said to be microlocally isotropic of order 2s if the covariance operator is a pseudo-differential operator with principal symbol given by µ(x)|ξ| −2s , where µ ≥ 0 is a smooth and compactly support function and is called the micro-correlation strength of the random function.…”
mentioning
confidence: 99%
“…Recently, a different model is proposed in [18,32] to describe random functions. The random function is considered to be a generalized Gaussian random function whose covariance is represented by a classical pseudo-differential operator.…”
mentioning
confidence: 99%
“…The authors studied an inverse problem for the two-dimensional random Schrödinger equation where the potential function was random. It is shown that the principle symbol of the covariance operator can be uniquely determined by the backscattered far field [18] or backscattered field [32], generated by a single realization of the random potential and plane waves [18] or a point source [32] as the incident field. A related work can be found in [25] where the authors considered an inverse scattering problem in a half-space with an impedance boundary condition where the impedance function was random.…”
mentioning
confidence: 99%
“…However, our study indicates that a single realization of the far-field measurement can be used to uniquely recover the variance function and the potential in certain scenarios. A crucial assumption to make the single-realization recovery possible is that the randomness is independent of the wave number k. Indeed, there are assorted applications in which the randomness changes slowly or is independent of time [5,20], and by Fourier transforming into the frequency domain, they actually correspond to the aforementioned situation. The single-realization recovery has been studied in the literature; see, e.g., [5,19,20].…”
Section: Introductionmentioning
confidence: 99%